Development of a Real-Time Data-Based Geographic Information System to Enhance Disaster Management: The Role of Media and Technology in Mitigation - Tarigan, M. Faisal Afiff (Universitas Islam Negeri Sumatera Utara, 2024)
In the digital era, information technology plays a crucial role in supporting disaster management. One of the increasingly utilized technologies is Geographic Information Systems (GIS), which enables interactive spatial data mapping. This study aims to design and develop a real-time data-based GIS system to provide up-to-date information, support rapid decision-making, and enhance early warning systems, thereby improving the resilience of Indonesian communities in facing disasters. The study employed the Research and Development (R&D) method to design a real-time data-based GIS system. The results indicate that this system enhances the effectiveness of disaster management in Indonesia. Based on trials, the system can deliver accurate and fast real-time data. For example, during a flood simulation, data on rising water levels and critical locations could be accessed in less than 30 seconds, enabling immediate mitigation measures. The system also fosters collaboration among government agencies, non-governmental organizations, and communities. During testing, 90% of participants reported that the interactive maps and evacuation route information helped them plan evacuation actions more effectively. This demonstrates that GIS technology not only supports emergency responders but also empowers communities by providing essential information for disaster preparedness.